SYARAT BERPENAMPILAN MENARIK PADA PENDAFTARAN CALON MAHASISWA SEBAGAI SALAH SATU DISKRIMINASI DI DUNIA PENDIDIKAN - Wiwin Saputri; H.R Adianto Mardijono (Gapenas Publisher, 2023)
The right to education is one of the Human Rights. That is, everyone has the right to access education. Education is a human right as well as a responsibility. The right to education is constitutionally guaranteed by the 1945 Constitution of the Republic of Indonesia (1945 Constitution). Even though the right to education has been guaranteed in such a way through various legal instruments, the implementation of education in Indonesia is still full of various obstacles. One of the obstacles that must be resolved is related to discrimination. The form of discrimination that is most often encountered is the inclusion of attractive appearance requirements for prospective students. Automatically, other prospective students who do not have these requirements cannot register. This is what is then referred to as discrimination and restrictions on the right to education. Based on this, it is interesting to analyze the legal protection for prospective students who receive discriminatory treatment according to Article 12 and Article 60 of Law Number 39 of 1999 concerning Human Rights. The research method used is normative legal research method. The research results show that the requirement to look attractive in the field of access to education is of course a violation of human rights